Lipid metabolic reprogramming in colorectal cancer: mechanisms and therapeutic strategies - Liu, Wujianhong; Dong, Shengrong; Hao, Feiran; Gao, Yaohui; Wei, Qing (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is the third most common cancer worldwide, and its high incidence, mortality, and treatment resistance highlight the urgency of exploring new therapeutic targets. As research into cancer metabolic reprogramming deepens, the central role of lipid metabolism abnormalities in CRC progression has gradually become apparent. In the tumor microenvironment (TME), conditions such as hypoxia, glucose deprivation, and lactic acid accumulation alter the energy demands of tumor cells, driving metabolic reprogramming in lipid uptake, synthesis, and oxidation. This reprogramming helps maintain high energy needs and supports the malignant growth of tumor cells. This lipid metabolic reprogramming provides tumor cells with the necessary energy and enhances their proliferation, invasion, immune evasion, and resistance characteristics. Moreover, the lipid metabolic reprogramming of tumor cells is closely related to various cells within the TME, and these interactions promote, to some extent, the remodeling of the tumor microenvironment, further driving tumor development. Emerging lipid detection technologies position specific lipid molecules as promising biomarkers for auxiliary diagnosis and prognostic evaluation. Concurrently, targeting key lipid metabolic pathways offers innovative strategies to optimize existing therapies and overcome drug resistance. This review summarizes the basic and abnormal mechanisms of lipid metabolism in CRC, lipid metabolic interactions in the tumor microenvironment, the regulatory network between the gut microbiota and lipid metabolism, and the progress in therapeutic strategies targeting lipid metabolism. By exploring the interaction between CRC and lipid metabolism in depth, this review aims to provide new ideas and theoretical support for the treatment, early intervention, and prognosis evaluation of CRC.